Pain And Disability In Secondary School Teachers - Correlation Study - B.SHARMILA,; JAGATHEESAN ALAGESAN, (International Journal of Pharma and Bio Sciences, 2015)
Non-specific neck pain is sudden-onset, bout of neck pain common in teachers. This correlation study was conducted to find out the relationship of various factors like age, teaching experience, travel distance, working hours per week, hours of lessons handled per week, hours of working with computer per week and hours of household work per week with pain and disability in secondary school teachers with non-specific neck pain. 249 teachers with non-specific neck pain were assessed for neck pain by Northwick Park Neck Pain Questionnaire, and Disability by Neck Disability Index. There was significant correlation between age and pain with p=0.011, experience and pain with p=0.002 and teaching experience and disability with p=0.020. There was significant negative correlation between working hours per week and pain with p=0.028 and hours of lessons handled per week and disability with p=0.028. This study concluded the existence of correlation between various factors with neck pain and disability.